I. D. Kabakov and the Ural Regionalism of the Late 1920-ies - mid 1930-ies - M. S. Kyrchikov (Научный диалог, 2017)
The activity of the Ural party-state leader in 1928-1937 years Ivan Dmitrievich Kabakov is considered. His role in the socialist transformation of the late 1920-ies - middle of 1930-ies is examined in the context of relations between the Centre and regions of the country, manifestations of regionalist trends, characteristics of industrial modernization. The urgency is determined by the appeal to the study of Soviet regional policy in the Urals of examined period through the prism of the interests of the region and assess the value of the personality of the leader of the Ural (Sverdlovsk since 1934) region. The author analyzes the influence of Kabakov initiatives on the development of “horizontal” economic ties. It is reported that he had provided maximum use of internal regional resources for local needs, upholding the positions of the Urals in the face of impending “centralization” of control and accelerated “industrialization.” One of the key findings of the study appears to be a statement about the importance of I. D. Kabakov as a political figure and business leader, who was built into the Soviet system of government, but who had considerable personal power, allowed to achieve a major production success that laid the image of the region for decades. Special role of the Urals in the territorial-economic complex of the country is emphasized.